2011
DOI: 10.1063/1.3606423
|View full text |Cite
|
Sign up to set email alerts
|

Observation of electron behavior in ambipolar polymer-based light-emitting transistor by optical second harmonic generation

Abstract: Articles you may be interested inStudy on copper phthalocyanine and perylene-based ambipolar organic light-emitting field-effect transistors produced using neutral beam deposition method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
(20 reference statements)
2
13
0
Order By: Relevance
“…In practice, this method has also been employed for the investigation of the electron behavior and carrier distribution of ambipolar OLETs. For example, it was found that EFISHG signals of polymer‐based ambipolar OLETs could be clearly observed at the point where the EL was generated . In terms of EFISHG, these investigations suggested that the highest enhancement of the electric field was on the zero‐potential position in the channel, which represented the meeting point of electrons and holes and was an origin of the EL.…”
Section: State‐of‐the‐art Strategies For High Performance Oletsmentioning
confidence: 98%
“…In practice, this method has also been employed for the investigation of the electron behavior and carrier distribution of ambipolar OLETs. For example, it was found that EFISHG signals of polymer‐based ambipolar OLETs could be clearly observed at the point where the EL was generated . In terms of EFISHG, these investigations suggested that the highest enhancement of the electric field was on the zero‐potential position in the channel, which represented the meeting point of electrons and holes and was an origin of the EL.…”
Section: State‐of‐the‐art Strategies For High Performance Oletsmentioning
confidence: 98%
“…To overcome this situation, experimental method that is capable of directly probing carrier motion is of great help. Accordingly, we have been developing an optical electric-fieldinduced second-harmonic generation (EFISHG) method that can directly probe carrier dynamics in organic devices, and have visualized carrier transport in organic field-effect transistors [3,4], and charge accumulation and decay processes at the interface in organic light-emitting diodes [5][6][7]. The EFISHG measurement was found very effective for tracing carrier behaviors in organic devices [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…21 Figure 1(a) portrays the structure of OLETs used in this experiment. First, the bottom-contact gold source and drain electrodes (25 nm thick) were deposited on a glass substrate using shadow mask.…”
mentioning
confidence: 99%
“…According to the EFISHG spectrum of F8BT films, the fundamental wavelength was fixed at 840 nm in this study. 21 The light source for the SHG measurement was a Nd:YAG laser-equipped with optical parametric oscillator (OPO:Continuum Surelite OPO). Spot size was approximately 100 lm, and fundamental light almost uniformly irradiated across the channel.…”
mentioning
confidence: 99%
See 1 more Smart Citation